The role of reflective p-contacts in the enhancement of light extraction in nanotextured vertical InGaN light-emitting diodes - Jang, Ho Won; Ryu, Seong Wook; Yu, Hak Ki; Lee, Sanghan; Lee, Jong-Lam (IOP PUBLISHING LTD, 2010)
We report effective methods for improving light extraction efficiency for n-side-up vertical InGaN light-emitting diodes (LEDs). For the LEDs with high reflectance Ag-based p-contacts, nanotexturing of the n-GaN surface using a combination of photonic crystals and photochemical etching drastically enhances the efficiency of extraction from the top surface. In contrast, the LEDs with low reflectance Au-based p-contacts show significantly less improvement through the nanotexturing. These experimental results indicate the critical role of high reflectance p-contacts as well as surface texturing in improving the light extraction efficiency of the vertical LEDs for solid-state lighting.
Keywords: EFFICIENCY; BLUE